Developing Consensus in the Assessment and Treatment Pathways for Autoimmune Encephalitis in Child and Adolescent Psychiatry - Mooneyham, GenaLynne C.; Ferrafiat, Vladimir; Stolte, Erin; Fuchs, D. Catherine; Cohen, David (Frontiers in Psychiatry, 2021)
Children with a diagnosis of Autoimmune Encephalitis (AE) frequently require multi-disciplinary care in order to mobilize the assessment and treatment necessary for recovery. Institutional and provider practice differences often influence the diagnostic workup and treatment pathways made available to patients. There are a variety of provider coalitions in pediatric rheumatology, internal medicine, and neurology that have been making meaningful progress towards the development of consensus in assessment and treatment approaches to patient care. However, child psychiatry is currently underrepresented in this work in spite of the high psychiatric symptom burden seen in some young patients. The need for consensus is often made visible only with inter-institutional dialogue regarding patient care trajectories. We aim to review key updates in the assessment and treatment of children and adolescents with autoimmune encephalitis during the acute phase, with or without catatonia, and to outline provider perspectives by comparing current treatment models in the United States, Canada, and Europe.